P557 Analysis of colectomy rates and advanced therapy prescribing for ulcerative colitis in Lothian; Scotland an updated population based cohort study. (30th January 2023) - Jenkinson, P; Plevris, N; Gros Alcalde, B; Lyons, M; Derikx, L; Constantine-Cooke, N; Arnott, I; Jones, G; Lees, C
Abstract: Background: The impact of advanced therapies on colectomy rates in UC remains unclear. We have published a population-based cohort reporting patterns of advanced therapy prescribing and the impact on colectomy rates complete to 2018 The aim of this study was to describe recent trends by extending the study period to 2021. Methods: The Lothian IBD registry (LIBDR) is a manually validated, comprehensive, population dataset of the Edinburgh area . The LIBDR contains measured point prevalence between 2008-2018 and estimated prevalence from 2018-2028 (derived from AARIMA modelling). All patients with a diagnosis of UC who commenced advanced therapy or underwent a colectomy in Lothian, Scotland between 01/01/2005 and 31/12/2021 were included interrogating multiple clinical and administrative databases. Linear and segmental regression analyses were used to identify the annual percentage change (APC) and temporal trends (statistical joinpoints) in colectomy rates and drug initiation. Kaplin Meier curves were created for drug ersistence and compared with the log rank test. Results: 484 patients underwent colectomy for UC between 2005 and 2021. Colectomy rates per 100 UC patients fell from 1.47 colectomies in 2005 to 0.25 in 2021 (p=0.009). Temporal trend analysis (2005-2021) identified a significant joinpoint in colectomy rates in 2014 (p=0.009) (Figure 2). Figure 1, Colectomy rates per 100 UC patients from 2005-2021. Joinpoint regression separated at inflection point at 2014 (dashed line). 383 patients were treated with their first advanced therapy for UC between 2005 and 2021, of whom 165 progressed to second line therapy. The annual percentage change in first line therapy was 34.7%, with joinpoints at 2013 and 2015 (p<0.001). Figure 2, First line advanced therapy prescription rate per 100 UC patients per year between 2005-2021 stratified by agent used. Figure 3, Second line advanced therapy prescription rate per 100 UC patients per year between 2005-2021 stratified by agent used. The 1 and 2 year persistence on first line advanced therapy was; 44.8% and 24.1% for adalimumab, 60.7% and 54.4% for infliximab and 79.8% and 67% for vedolizumab (p=0.001) (Fig 3). Fig 4, Persistence on first line advanced therapy. Conclusion: This population based cohort study has shown a significant increase in advanced therapy prescription for UC. Whilst we cannot ascribe causality this has been paralleled by a significant reduction in the rate of colectomy that has been maintained in recent years.